If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 11n = 15 + 9n Solving -5 + 11n = 15 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -5 + 11n + -9n = 15 + 9n + -9n Combine like terms: 11n + -9n = 2n -5 + 2n = 15 + 9n + -9n Combine like terms: 9n + -9n = 0 -5 + 2n = 15 + 0 -5 + 2n = 15 Add '5' to each side of the equation. -5 + 5 + 2n = 15 + 5 Combine like terms: -5 + 5 = 0 0 + 2n = 15 + 5 2n = 15 + 5 Combine like terms: 15 + 5 = 20 2n = 20 Divide each side by '2'. n = 10 Simplifying n = 10
| 3y=3y-5 | | x-0.6=8.98 | | 9+9n= | | 8-4y=7 | | 2x/5+43/5=3 | | 9(x-3)=-3(x+-4)+47 | | 7=2q-1/3(-3q+3) | | -6u=-6 | | 4(2x-3)-3(5x-1)=2(3x-24) | | -1-7=x | | 2q=3q-9 | | V^2=48 | | 4(3-5/6m)=32/3 | | 29z=-232 | | 5(x-2)=-7(x+3)+38 | | 4x/8+64/8=5 | | 80-7.94x=40.30 | | 10+7d-15=10-2d-7+5d | | 25-4y=3 | | -6r+7=4r+7 | | 3(2x+4)+2(9x-2)=2(3x+13) | | 30=8x+30 | | 4x/7+37/7=-5 | | 12-2x=-5x+18 | | 4(3-5/6m)=32/2 | | 16.95+.78x=156.57 | | 2(x+3)=6x-16 | | 10y-6+2y=9+11y-4 | | 3(5/11)+2y=4 | | 9x+5-2x+2=5x-2x+21-2 | | 3/7y=6 | | 12x-3=12x+6 |